2022
DOI: 10.3390/en15051852
|View full text |Cite
|
Sign up to set email alerts
|

Justifying Short-Term Load Forecasts Obtained with the Use of Neural Models

Abstract: There is a lot of research on the neural models used for short-term load forecasting (STLF), which is crucial for improving the sustainable operation of energy systems with increasing technical, economic, and environmental requirements. Neural networks are computationally powerful; however, the lack of clear, readable and trustworthy justification of STLF obtained using such models is a serious problem that needs to be tackled. The article proposes an approach based on the local interpretable model-agnostic ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Electrical consumption is often influenced by different climatic factors, such as temperature and humidity [2]. Therefore, the short-term prediction models often include meteorological and temporal parameters [5], [39], temperature and wind speed [40], humidity and total precipitable liquid water [41]. Additionally, there is a distinction between working days and weekends or holidays because they show different electrical load-consuming profiles.…”
Section: Methodsmentioning
confidence: 99%
“…Electrical consumption is often influenced by different climatic factors, such as temperature and humidity [2]. Therefore, the short-term prediction models often include meteorological and temporal parameters [5], [39], temperature and wind speed [40], humidity and total precipitable liquid water [41]. Additionally, there is a distinction between working days and weekends or holidays because they show different electrical load-consuming profiles.…”
Section: Methodsmentioning
confidence: 99%
“…Kim et al's explanation of the energy demand forecast model employing feature importance and attention methods was published in [44]. To support and elucidate the forecasts, Grzeszczyk et al [56] suggested a strategy based on the LIME method. Both Wenninger et al [59] and Moon et al [58] used distinct and ante hoc XAI techniques with feature-important analysis.…”
Section: Energy and Building Managementmentioning
confidence: 99%
“…On bigger scale (e.g. distribution or national load forecasting), these variations compensate themselves and the same tools can achieve better accuracy [15] (best known nowadays around 3-5% for national scale [23] ).…”
Section: Self-updating Building Load Forecasting Systemmentioning
confidence: 99%